The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1063/1.4990547
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian nonparametric approach to reconstruction and prediction of random dynamical systems

Abstract: We propose a Bayesian nonparametric mixture model for the reconstruction and prediction from observed time series data, of discretized stochastic dynamical systems, based on Markov Chain Monte Carlo methods. Our results can be used by researchers in physical modeling interested in a fast and accurate estimation of low dimensional stochastic models when the size of the observed time series is small and the noise process (perhaps) is non-Gaussian. The inference procedure is demonstrated specifically in the case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…The novelty of our approach lies on the fact that we make no parametric assumptions for the density of the noise component. Instead, we model the additive error using a highly flexible family of density functions, which are based on a Bayesian nonparametric model, namely the Geometric Stick Breaking process [8], extending previous works regarding reconstruction and prediction of random dynamical systems [13,14,23]. No matter what additive errors are involved, we are confident that our family of densities will be able to capture the right shape and hence statistical inference, for the parameters of interest will be improved and reliable.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The novelty of our approach lies on the fact that we make no parametric assumptions for the density of the noise component. Instead, we model the additive error using a highly flexible family of density functions, which are based on a Bayesian nonparametric model, namely the Geometric Stick Breaking process [8], extending previous works regarding reconstruction and prediction of random dynamical systems [13,14,23]. No matter what additive errors are involved, we are confident that our family of densities will be able to capture the right shape and hence statistical inference, for the parameters of interest will be improved and reliable.…”
Section: Introductionmentioning
confidence: 91%
“…, N n ) (see Ref. [23], and references therein). The d i random variable, denotes the component of the random mixture f in (5), that the observation x i came from.…”
Section: The Posterior Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally we randomize the probability-weights by letting λ ∼ Be(α, β); then λ a-posteriori is again beta with its parameters updated by a sufficient statistic of the data. In Merkatas, Kaloudis, and Hatjispyros (2017) it is shown that a G-based Bayesian nonparametric framework for dynamical system estimation is efficient, faster and less complicated when compared to Bayesian nonparametric modeling via the Dirichlet process.…”
Section: Preliminariesmentioning
confidence: 99%
“…1. Approximate the quasi-invariant measure, of the underlying random dynamic system, thus implying the existence of a prediction barrier [26].…”
Section: Introductionmentioning
confidence: 99%